Conceptuality of Rational and managerial Rationality An Analytical Study - I.H Al-Zaydi, Qais. (International Journal of Psychosocial Rehabilitation, 2020)
Organizations and organizational behavior requirements are of distinct importance in managerial thought in general, inasmuch their association with the present of organizations and their desirable future in light of the unprecedented and rapid environmental challenges that are difficult to determine their effects on organizations. In this environment, the importance of highlighting the essential of some terms emerged in order to explain the decisions and actions that lead organizations and the extent of their effectiveness that are reflected in organizational actions in general. Among these terms is the term “rationality”, which has the main role in indicating the quality of behavior and decision-making in the same time, and what this term enjoys of extreme privacy, which is not only at the level of management science but rather for the rest of the sciences that reflect the dominant values and beliefs and what is related in this concern, the confusion and complexity in finding the correct concept for it. The current study comes to represent a serious attempt to focus on the philosophical aspects of this term through an analytical concentration of the views of the pioneers and philosophers in management and organizational thought and to answer the question related to what is rational or irrational in the world of organizations in general.